(untitled) (MCIT: Proceedings of International scientific and practical conference, 2023)
This report is devoted to aspects of the application and improvement of methods of geoinformation systems and information technologies to solving problems of hydromorphodynamics for the development of measures to ensure the stable state of the sea approach channels looking on the example of the deepwater Danube-Black Sea shipping channel. Mathematical numerical methods with a GIS database were used for modeling river and coastal processes, creating calculation grids and postprocessing the numerical results.